Interlocking Constitutions : Towards an Interordinal Theory of National, European and UN Law. - Gordillo, Luis I. (Hart monographs in transnational and international law., 2012)
The existence of interactions between different but overlapping legal systems has always presented challenges to black letter law. In this book Pérez analyses the inter-ordinal instabilities which arise at the European level, focusing on three main strands of case-law and their implications: Solange, Bosphorus and Kadi.